2020
DOI: 10.1002/anie.201912613
|View full text |Cite
|
Sign up to set email alerts
|

An Unexpected Transannular [4+2] Cycloaddition during the Total Synthesis of (+)‐Norcembrene 5

Abstract: We report a concise and versatile total synthesis of the diterpenoid (+)‐norcembrene 5 from simple building blocks. Ring‐closing metathesis and an auxiliary‐directed 1,4‐addition are the key steps of our synthetic route. During the synthesis, an unprecedented, highly oxidized pentacyclic structural motif was established from a furanocembranoid through transannular [4+2] cycloaddition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
3
8
0
Order By: Relevance
“…after reflux in benzene (Scheme 6). 9 A similar reactivity was observed by Pattenden during the attempted total synthesis of plumareillide, in this case postulating the transannular Diels Alder reaction as part of the biosynthetic pathway to this secondary metabolite. 10…”
Section: Accepted Manuscriptsupporting
confidence: 71%
See 1 more Smart Citation
“…after reflux in benzene (Scheme 6). 9 A similar reactivity was observed by Pattenden during the attempted total synthesis of plumareillide, in this case postulating the transannular Diels Alder reaction as part of the biosynthetic pathway to this secondary metabolite. 10…”
Section: Accepted Manuscriptsupporting
confidence: 71%
“…This is the case of the attempt to access the norcembrenolide diterpenic scaffold in which a furane-containing macrocycle underwent this transannular process converted slowly upon standing into a complex polycyclic highly oxygenated adduct or in 80 minutes after reflux in benzene (Scheme 6). 9 A similar reactivity was observed by Pattenden during the attempted total synthesis of plumareillide, in this case postulating the transannular Diels-Alder reaction as part of the biosynthetic pathway to this secondary metabolite. 10 Scheme 6 Transannular Diels-Alder reaction employed to build the decaline core of verongidolide In fact, it has been demonstrated that a 'Diels-Alderase' enzyme is involved in the acceleration of a transannular [4+2] cycloaddition during the biosynthesis of natural product spynosyn A (Scheme 7).…”
Section: Scheme 5 Transannular Diels-alder Reaction Employed To Build...supporting
confidence: 70%
“…a | iso-epicolactone (92) [75,76] , (+)brevianamide Y (93), [77][78][79] (±)-desoxyisobruceol (94) [80][81][82][83] , and (-)-prehalenaquinone (95) [84] are additional examples for molecules that were synthesized in the laboratory prior to their isolation. b | Cases of anticipated natural products that await isolation from natural sources: 8-epi-isoaplydactone (96), [85] dia-angiopterlactone B (97), [86] biyouyanagin C (98), [87] epi-pycnanthuquinone C (99), [88] 8-epi-homodimericin A (100), [89] intricarene side-product (101), [90] protected dia-millingtonine (102) [91] , diaincargranine B aglycone (103) [92] , diastereomer towards neonectrolides (104) [93] , preuisolactone precursor (105) [94] , nuphar alkaloid isomer (106) [95] , side-product towards (+)-norcembrene 5 (107) [96] , monolomaiviticin A (108) [97] , 2-epilankacyclinol (109) [98] , 3,7-epi-massadine (110) [99] , santarubin S (111) [100] , epiguajadial B (112) [101] , Δ 23,24 -perovskone (113) [102] , epi-pungiolide A (114) [103] , and iso-aspergilasine A (115) [104] . This review cannot be comprehensive since it relies mostly on our own experience in the field of biomimetic natural product synthesis and is limited by difficulties in finding diffuse information in the vast chemical literature.…”
Section: Discussionmentioning
confidence: 99%
“…Whileas, Gaich's team presented the first total synthesis of (+)‐Norcembrene 5 532 (Scheme 80), a diterpenoid with 14‐membered cembrane framework where the RCM was employed as one of the decisive step to construct the 14‐membered macrocyclic ring system [261] . Herewith, Wittig olefination of aldehyde 529 with MePPh 3 Br and LiHMDS afforded a diene 530 , which fruitfully endured to the ring closing metathesis with G‐II catalyst 2 and delivered a macrocyclic compound 531 .…”
Section: Ring‐closing Metathesis (Rcm)mentioning
confidence: 99%
“…Whileas, Gaich's team presented the first total synthesis of (+)-Norcembrene 5 532 (Scheme 80), a diterpenoid with 14membered cembrane framework where the RCM was employed as one of the decisive step to construct the 14-membered macrocyclic ring system. [261] Herewith, Wittig olefination of tides with a 12-membered macrolactone linked to a long alkyl chain, isolated from the endophytic actinomycete Actinoallomurus fulvus MK10-036 and possess a strong profile against Trypanosoma protozoan parasites. [262] In this synthetic strategy, they employed an RCM protocol as the key transformation to construct the 12-membered macrolactone.…”
Section: Total Synthesis Of Natural Products Based On Rcmmentioning
confidence: 99%